2006
DOI: 10.1073/pnas.0605303103
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for TPP1 and TIN2 interaction in high-order telomeric complex assembly

Abstract: Mammalian telomeric proteins function through dynamic interactions with each other and telomere DNA. We previously reported the formation of a high-molecular-mass telomeric complex (the mammalian telosome) that contains the six core proteins TRF1, TRF2, RAP1, TIN2, POT1, and TPP1 (formerly named PTOP͞PIP1͞ TINT1) and mediates telomere end-capping and length control. In this report, we sought to elucidate the mechanism of six-protein complex (or shelterin) formation and the function of this complex. Through rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
237
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(249 citation statements)
references
References 48 publications
8
237
2
2
Order By: Relevance
“…Although the phosphorylation site in TRF1 identified here fails to exactly resemble the Plk1 consensus phosphorylation sequence (D/E)X(S/T)⌽ (X, any amino acid; ⌽, a hydrophobic amino acid) (21,35), the sequence context of TRF1-Ser-435 is similar to that identified in other substrates of Plk1 in our laboratory: ESSY 720 in Topors 3 and TASE 195 in CLIP-170. 4 Thus, an aspartic acid or glutamic acid at the ϩ1 or Ϫ1 position appears to be important for phosphorylation of substrates by Plk1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the phosphorylation site in TRF1 identified here fails to exactly resemble the Plk1 consensus phosphorylation sequence (D/E)X(S/T)⌽ (X, any amino acid; ⌽, a hydrophobic amino acid) (21,35), the sequence context of TRF1-Ser-435 is similar to that identified in other substrates of Plk1 in our laboratory: ESSY 720 in Topors 3 and TASE 195 in CLIP-170. 4 Thus, an aspartic acid or glutamic acid at the ϩ1 or Ϫ1 position appears to be important for phosphorylation of substrates by Plk1.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that casein kinase 2 is a TRF1 kinase in vitro, and our mapping experiments indicated that Ser-435 is not the phos-3 X. Yang and X. Liu, unpublished data. 4 H. Li and X. Liu, unpublished data. C-E, Plk1 depletion reduces TRF1 binding to telomeres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A crucial way in which shelterin is thought to affect the structure of telomeric DNA is by forming t-loops. This complex is composed of six proteins including TRF1 (7,8), TRF2 (9), POT1 (10), TIN2 (11), TPP1 (12), and Rap1 (13). TRF2 binds directly to the tandem array of duplex TTAGGG repeats and coats the length of all human telomeres at all stages of the cell cycle (9,14).…”
Section: Introductionmentioning
confidence: 99%